Kilquist syndrome: A novel syndromic hearing loss disorder caused by homozygous deletion of SLC12A2. Issue 5 (12th March 2019) - Macnamara, Ellen F.; Koehler, Alanna E.; D'Souza, Precilla; Estwick, Tyra; Lee, Paul; Vezina, Gilbert; ,; Fauni, Harper; Braddock, Stephen R.; Torti, Erin; Holt, James Matthew; Sharma, Prashant; et al.
Abstract: Syndromic sensorineural hearing loss is multigenic and associated with malformations of the ear and other organ systems. Herein we describe a child admitted to the NIH Undiagnosed Diseases Program with global developmental delay, sensorineural hearing loss, gastrointestinal abnormalities, and absent salivation. Next‐generation sequencing revealed a uniparental isodisomy in chromosome 5, and a 22 kb homozygous deletion in SLC12A2, which encodes for sodium, potassium, and chloride transporter in the basolateral membrane of secretory epithelia. Functional studies using patient‐derived fibroblasts showed truncated SLC12A2 transcripts and markedly reduced protein abundance when compared with control. Loss of Slc12a2 in mice has been shown to lead to deafness, abnormal neuronal growth and migration, severe gastrointestinal abnormalities, and absent salivation. Together with the described phenotype of the Slc12a2 ‐knockout mouse model, our results suggest that the absence of functional SLC12A2 causes a new genetic syndrome and is crucial for the development of auditory, neurologic, and gastrointestinal tissues. Abstract : These authors identified a novel, syndromic hearing loss disorder caused by homozygous loss of SLC12A2. Characteristic features include sensorineural hearing loss, global developmental delay, gastrointestinal abnormalities, and absent salivation; a similar presentation is present in Slc12a2‐knockout mice.